Microstructure, mechanical properties and sliding wear behaviour of thermally sprayed cermet coatings - Younis, Alhammali A.A. (2016)
Thermally sprayed tungsten carbide cermet coatings are extensively used in engineering applications, such as cutting tools, rock and earth drilling tools. When coatings are compared, they often differ in a number of ways, such as being deposited from powder feedstock with different characteristics (e.g. particle size, powder porosity, method of manufacture, different carbide grain sizes, different volume fractions of binder, different binder types) and with different thermal spray systems. When a number of factors are varied at once, then it is very difficult to identify the causes of any differences observed in coating microstructure and performance.